Serum biochemical profile in patients with decompensated heart failure with preserved ejection fraction depending on obesity - Timofeev, Yu. S.; Metelskaya, V. A.; Ivanova, A. A.; Dubovskaya, N. I.; Rogozhkina, E. A.; Vedenikin, T. Yu; Zamyatin, R. A.; Borisova, A. L.; Dzhioeva, O. N.; Drapkina, O. M. (Kardiovaskuli͡a︡rnai͡a︡ terapii͡a︡ i profilaktika, 2025)
Aim . To analyze a complex of cardiac markers, adipocytokines, heat shock proteins (HSPs) and extracellular matrix remodeling biomarkers in patients with acute decompensated heart failure with preserved ejection fraction (ADHFpEF) depending on the presence and degree of obesity. Material and methods . A total of 151 patients with ADHFpEF aged 47-95 years were divided into 2 following groups: main group — 85 patients with ADHFpEF and obesity (body mass index ≥30 kg/m 2 ); comparison group — 66 patients with ADHFpEF without obesity (body mass index <30 kg/m 2 ) as the comparison group. The level of biochemical blood parameters was determined using routine biochemical methods on BS800M1 (Mindray, China) and Maglumi 2000 (Snibe, China) systems, as well as by the enzyme immunoassay using a Multiskan FC photometer (Thermo, USA) and reagent kits from Vector-Best (Russia), Ray-Biotech (USA), Cloud-Clone (China), DBC (Canada) and Biovendor (Czech Republic). Results. In patients with ADHFpEF and obesity, significantly highermedian leptin levels and leptin/adiponectin ratio were found than in patients with ADHFpEF without obesity, while adiponectin and HSP70 levels in obesity were significantly lower. The median [Q25-Q75] HSP27 concentration in morbid obesity was 4,7 [1,2-24,2] ng/ml and was statistically significantly higher than in patients with class I and II obesity — 1,3 [0,3-2,7] and 0,6 [0,3-1,3] ng/ml, respectively. In patients with ADHFpEF with epicardial fat thickness ≥5 mm, not only higher leptin concentration and leptin/adiponectin ratio were found, but also increased blood myoglobin levels. Conclusion. We revealed a number of obesity-related serum biochemical features in patients with ADHFpEF, including differences in the main adipocytokine complex parameters, as well as cellular stress biomarkers — HSP27 and HSP70. This may indicate the involvement of obesity in heart failure pathogenesis and the pathophysiological processes in heart failure decompensation.